Features of active power definition in high-current pulsed discharge - Hrechko, Ya.O; Azarenkov, N.A.; Babenko, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Shovkun, M.A.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2016)
The calculation method of active power dynamics in high-current plasma diode has been presented in this paper. The main features that should be considered in the calculations have been identified. It is shown that it is possible to obtain the high power levels (over 100 MW) at a slight stored energy of capacitor bank (up to 200 J) under the conditions of the space charge double layer formation in the plasma.